EDUCATION IN DENTAL HEALTH FOR DISABLED CHILDREN'S MOTHERS:A SPACE FOR NURSING PRACTIONERS - Gislene Marcelino; Vinícius Alves Parrilha (Universidade Federal do Paraná, 2007)
Health education means to change attitudes and behaviors, forming health habits in the population on their own behalf.Through answers of disabled children's mothers assisted byAPAE ofAraçatuba-SP, there was an attempt to evaluate the perception ofthose mothers regarding dental health. Out of the 60 interviewed mothers, 88% said to know what causes cavities; 33.33% answeredthat cavity is a transmissible disease; and as for fluoride, 65.63% said that it is to prevent cavities. Besides the referred information,they were also asked about their knowledge concerning the first permanent molar, about the night breast-feeding, about the diet and thebrushing. Considering that mothers have a major role in the family, it's been concluded that their involvement is extremely importantin educational programs on dental health, so that they can act as multiplier agents of information that seek the promotion of their healthand their families'.